2022
DOI: 10.3390/vaccines10081234
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Studies of a Trivalent Vaccine Containing PCV-2a, PCV-2b Genotypes and Mycoplasma hyopneumoniae When Administered at 3 Days of Age and 3 Weeks Later against Porcine Circovirus 2 (PCV-2) Infection

Abstract: Four studies under preclinical and clinical conditions were performed to evaluate the efficacy of a new trivalent vaccine against Porcine circovirus 2 (PCV-2) infection. The product contained inactivated PCV-1/PCV-2a (cPCV-2a) and PCV-1/PCV-2b (cPCV-2b) chimeras, plus M. hyopneumoniae inactivated cell-free antigens, which was administered to piglets in a two-dose regime at 3 days of age and 3 weeks later. The overall results of preclinical and clinical studies show a significant reduction in PCV-2 viraemia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Circovirus diseases are widespread in pigs farming in almost all countries of the world, and Russia is no exception. Meanwhile vaccination is the main way of preventing viral infection [12,15].…”
Section: Histological Features Of the Livermentioning
confidence: 99%
See 2 more Smart Citations
“…Circovirus diseases are widespread in pigs farming in almost all countries of the world, and Russia is no exception. Meanwhile vaccination is the main way of preventing viral infection [12,15].…”
Section: Histological Features Of the Livermentioning
confidence: 99%
“…According to [15], PCV2 in animals affects lymphoid tissue. In the lungs the lymphoid tissue is associated with the bronchi, ensuring the flow of immune reactions.…”
Section: Histological Features Of the Livermentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some studies showed a closer genetic and antigenic relation between PCV-2b and PCV-2d sequences compared to PCV-2a and PCV-2d sequences [20,23]. Hence, a bivalent vaccine containing PCV-2a and PCV-2b genotypes may be a relevant option to face against the several PCV-2 genotypes that are circulating under field conditions [25,26]. In addition to PCV-2, Mycoplasma hyopneumoniae (M. hyopneumoniae) is also an important pathogen that usually circulates in pigs during the postweaning period.…”
Section: Introductionmentioning
confidence: 99%
“…Different PCV-2 vaccination regimens are already studied and commercialised. In fact, this chimeric vaccine has already shown efficacy in pre-clinical and clinical trials applied in a split-dose immunisation regime at three days of age and three weeks later [26]. This latter regime is especially interesting in those farms where PCV-2 infection is detected at early stages of life (lactating or early nursery periods) or when herd immunity is poor.…”
Section: Introductionmentioning
confidence: 99%